Privolzhsky District of Kalmyk Autonomous Oblast: Implementing Collectivization Policies - Namsyr A. Shikhanov1 (Oriental Studies)
Introduction. The article examines some peculiarities of Kalmykia’s mass agricultural collectivization through the example of Privolzhsky District characterized by the presence of three sectors — animal husbandry, fishing and crop farming. Goals. The study seeks to identify and analyze distinctive features of collectivization arrangements in Privolzhsky District. Materials and methods. The paper focuses on records management files and correspondence between government agencies and kolkhozes, economic and statistical accounts housed at Kalmykia’s National Archive (coll. Р-3, Р-37 and Р-112). The documents narrate about collectivization efforts undertaken in the district during the period in question, show the actual dynamics of economic indicators, and describe related social processes. The work employs the historical genetic and comparative methods. Results. In the early to mid-1930s, the Soviets would intensively pursue collectivization and sedentarization policies across Privolzhsky District. The collectivization acceleration measures included confiscation of property owned by the rich. Once privileged groups of Privolzhsky District would be relocated to a newly established kulak settlement in Primorsky District and other regions of the country. The local kolkhoz network grew to a total of 9 units that focused on animal husbandry. The share of kolkhoz-employed villagers increased (67,6 % in 1932) and, accordingly, that of self-employed ones decreased (32,4 %). At large, the collectivization efforts across the designated district did yield agricultural output growth for selected items by the mid-1930s.